2017
DOI: 10.3390/ijms18020278
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis Activates Endoplasmic Reticulum Stress Pathways through GPR4 in Human Vascular Endothelial Cells

Abstract: Acidosis commonly exists in the tissue microenvironment of various pathophysiological conditions such as tumors, inflammation, ischemia, metabolic disease, and respiratory disease. For instance, the tumor microenvironment is characterized by acidosis and hypoxia due to tumor heterogeneity, aerobic glycolysis (the “Warburg effect”), and the defective vasculature that cannot efficiently deliver oxygen and nutrients or remove metabolic acid byproduct. How the acidic microenvironment affects the function of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 34 publications
(136 reference statements)
2
81
0
Order By: Relevance
“…[97][98][99][100] Other examples include acidosis activation of GPR4 in the vascular endothelial cell inflammatory response. 101,102 Pyk2 regulates coupling of receptor proteins to MAPK signaling pathways, such as integrins, GPRs, vascular endothelial growth factor receptor, and EGF receptor. 103 Additionally, Pyk2 is involved in signaling pathways entailing both ET and angiotensin II, and the control of vasoconstriction and BP.…”
Section: Molecular Response To Acid Retention: Sensors Of the Acid-bamentioning
confidence: 99%
“…[97][98][99][100] Other examples include acidosis activation of GPR4 in the vascular endothelial cell inflammatory response. 101,102 Pyk2 regulates coupling of receptor proteins to MAPK signaling pathways, such as integrins, GPRs, vascular endothelial growth factor receptor, and EGF receptor. 103 Additionally, Pyk2 is involved in signaling pathways entailing both ET and angiotensin II, and the control of vasoconstriction and BP.…”
Section: Molecular Response To Acid Retention: Sensors Of the Acid-bamentioning
confidence: 99%
“…It has been reported that GPR4 is involved in the regulation of acid-base balance and kidney acid secretion (6). Acidosis may activate the expression of GPR4 in order to regulate the expression of the genes involved in different biological pathways, including the ERS response and cell metabolism (3,21). A previous study demonstrated that acidosis/GPR4 regulated endothelial cell adhesion through cAMP production and served a role in the inflammatory response of vascular endothelial cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ischemic and hypoxic conditions of the tumor microenvironment activates GPR4 and thereby promotes angiogenesis. Another study with ECs demonstrated that GPR4 promotes angiogenesis via the regulation of C/EBP homologous protein (CHOP) in an acidic environment (45). Although these studies have shown that GPR4 promotes angiogenesis, the role of GPR4 in liver cancer was not investigated.…”
Section: Discussionmentioning
confidence: 99%